A Portable Noncontact Profile Scanning System for Aircraft Assembly. (August 2022) - Liang, Bing; Liu, Wei; Liu, Kun; Zhou, Mengde; Zhang, Yang; Jia, Zhenyuan
Highlights: A hybrid measurement system based on camera and proximity sensors is developed. A profile-driven automated scanning strategy is proposed. The developed system can scan large profiles efficiently and automatically. Abstract: Three-dimensional (3D) profile scanning plays a crucial role in the inspection of assembled large aircraft. In this paper, to achieve noncontact automatic measurements of the high-reflective profiles of large-scale curved parts and components, an automated noncontact system and method with high accuracy and high efficiency are presented. First, a hybrid 3D coordinate measurement system based on proximity sensors and cameras is proposed to obtain noncontact measurements while avoiding the influence of high reflection on the measurement accuracy. A hybrid measurement model that combines the one-dimensional distances measured by the proximity sensors and the 3D information obtained by cameras is proposed to determine high-accuracy 3D coordinates of the measured points. Then, a profile-driven 3D automated scanning method and strategy are designed to rapidly scan and reconstruct the profile within the effective range without scratching the profile or exceeding the measurement range of the proposed system. Finally, experiments and accuracy analyses are performed in situ on an assembled tailplane panel (approximately 1760 mm × 460 mm). The automated scanning process is completed in a timeframe of 208 s with an average error of less than 0.121 mm for profile reconstruction. Therefore, the proposed method is promising considering both the high accuracy and high efficiency requirements of profile inspections for large aircraft.